Evaluation of the compression process diagram in presence of magnesium stearate - Hossein Asgarirad; Claus Führer (Pharmaceutical and Biomedical Research, 2015)
In the pharmaceutical industry is no longer worked without instrumented tablet presses. The recording of the press information at different parameters of each test series and batches in the development of tablets and an online measurement and control of pressing forces during the production process is becoming increasingly important. Eccentric tablet presses were equipped with sensors for the upper and lower punch force and upper punch way. As sample quantity 100g were selected. All fillers lubricant mixtures were prepared in Turbula lab mixtures with 68 rpm. The bulk and tap density of the excipients were determined according to DIN of 53912 and 53194 on a tap density testers into a 250 ml graduated cylinder. It is to be expected that compression diagrams are changed by lubricant additives. This should give itself to recognize in the different section of the force relationship. This study also showed that the lubricant properties of a lubricant can be greatly influenced by the interaction between the lubricant and ingredient formulation to be exposed.